1994
DOI: 10.1107/s0108768193005713
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and molecular structures of pyridazinone cardiovascular agents

Abstract: The crystal and molecular structures of 11 6-substituted pyridazinone derivatives: 6-phenyl-3(2H)-pyridazinone-acetic acid (1/1) (1), 6-(4-aminophenyl)- 3(2H)-pyridazinone (2), 6-(4-aminophenyl)- 5-methyl-3(2H)-pyridazinone (3), 6-(4-acetamidophenyl)- 3(2H)-pyridazinone (4), 6-(4-acetamido-2- methoxyphenyl)-3(2H)-pyridazinone (5), 6-(2-aminophenyl)-3(2H)- pyridazinone (6), 6-phenyl-3(2H)- pyrazinone (7), 6-(4-aminophenyl)-4,5-dihydro- 3(2H)-pyridazinone (8), (R)-(-)-6[4-(3-bromopropionamido)phenyl]- 4,5-dihydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 5 publications
4
6
0
1
Order By: Relevance
“…Initial modelling and minimisation of the specific PDE III inhibitors showed that most of them had essentially planar conformations. This is in agreement with previous studies [14] which propose a generally flat topology for specific PDE III inhibitors, and the molecular geometry in the crystal of many inhibitors of phosphodiesterase III [15].…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…Initial modelling and minimisation of the specific PDE III inhibitors showed that most of them had essentially planar conformations. This is in agreement with previous studies [14] which propose a generally flat topology for specific PDE III inhibitors, and the molecular geometry in the crystal of many inhibitors of phosphodiesterase III [15].…”
Section: Methodssupporting
confidence: 82%
“…The best over!ay of the alternative conformation(with the acetyl group rotated in a trans conformation, to mimic SK&F95800), SK&F93741ac, matches different points and gives a comparable rmsd value, with only two moderate clashes. SK&F95800 is a better inhibitor than SK&F93741, despite the fact that it lacks a methyl group which is known to increase inhibitory activity [15]. Hence, it is not necessary to assume that SK&F93741 adopts the higher energy conformation, analogous to SK&F95800, in order to have an electrostatically favourable binding orientation.…”
Section: Skandf93741mentioning
confidence: 99%
“…1); structural parameters agree with those of known dihydropyridazinone derivatives [30]. HÀC(2) resonated at much higher field than to HÀC(3).…”
supporting
confidence: 66%
“…Hydrogen-bond topology: hydrogen-bond connectivities represented by means of: (a) our notation described in the text; (b) EMIl notation (Etter et ai., 1990); (c) EMB notation but taking into account RAHB (Gilli et al, 1989). Mastropaolo, Camerman & Camerman (1991); (k) Ohms, Guth, Hellner, DannOhl & Schweig (1984); (/) Schmalle, H~ggi & Dubler (1988); (m) Prout et al (1994); (n) Ferretti, Bertolasi, Gilli & Borea (1985); (o) Boer (1972); (t7) Bradshaw, Guynn, Wood, Wilson, Dalley & Izatt (1987); (q) Lowe, Schwalbe & Williams (1987); (r) Low, Tollin, Brand & Wilson (1986); (s) Watt, Martin, Duchamp, Mizsak, Nielson & Prairie (1988); (t) Smith, Bobe, Minnetian, Hope & Yanuck (1985). In the remaining examples (7 and 35-39), N.--O distances are rather short (2.734-2.856,~,), although the C:O and NH moieties apparently belong to a O---C--C--NmH non-conjugated moiety.…”
Section: -O Intermolecular Hydrogen Bondingmentioning
confidence: 99%